The Influence of Al-Farabi on the Poetry of Arabic Wisdom (Journal of Oriental Studies, 2020)
Everyone knows the contribution that al-Farabi made to the study of not only Arabic philosophy but also world philosophy, in addition to its influence in logic, music, politics, medicine, mathematics, astronomy, classification and other sciences. But did al-Farabi influence Arab poetry - the first Arab art? The main goal of this article is to find answers to questions about the influence of al-Farabi on Arabic poetry and the degree of its manifestation, to study the effects of this influence. The study that we have in our hands is trying to answer these questions based on the relationship between the great philosopher and the stream of wisdom in Arabic poetry, which extends from the pre-Islamic era to the Abbasid era, beginning with the greatest Arab poet Abi al-Tayyib al-Mutanabbi, and for followed by Arab poets of wisdom, such as Abu Ala al-Maari, the Honorable Sheriff and Ibn al-Wardi in the Middle Ages and poets Ahmed Shawki, al-Gohari and al-Barduni in the modern era. The study used methods of comparative analysis, material collection, and data classification. The article draws the main conclusions about the influence of al-Farabi on the poetry of the wisdom of Arabic literature and provides a comparative and intertextual analysis of poetic works. Key words: Al-Farabi, Lord, Islam, Arabic poetry of wisdom, philosophy, al-Mutanabbi.